2020
DOI: 10.1177/0194599820929275
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized Particle Reduction: A Novel Cadaveric Model and a Negative Airway Pressure Respirator (NAPR) System to Protect Health Care Workers From COVID‐19

Abstract: Objectives This study aimed to identify escape of small-particle aerosols from a variety of masks using simulated breathing conditions. This study also aimed to evaluate the efficacy of a negative-pressure environment around the face in preventing the escape of small aerosolized particles. Study Design This study is an evaluation study with specific methodology described below. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 11 publications
(29 reference statements)
1
21
0
Order By: Relevance
“…In line with results from previous work by Khoury, 19 we demonstrated a significant emission of aerosolized particles without a mask. Table I summarizes the white pixel count for the final subtraction image in each scenario.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In line with results from previous work by Khoury, 19 we demonstrated a significant emission of aerosolized particles without a mask. Table I summarizes the white pixel count for the final subtraction image in each scenario.…”
Section: Resultssupporting
confidence: 93%
“…In the only other study to use smoke simulation of droplet nuclei, Khoury et al 19 used incense Joss sticks to generate aerosol particles of a diameter of 0.28 μm 26 . They also demonstrated that their Negative Airway Pressure Respirator (NAPR) was able to prevent aerosol escape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that their negative airway respirator (NAPR), designed by drilling a small hole in the plastic bottom of a standard Ambu mask and inserting a suction tubing, allowed no particles to escape. 52 Dharmaraian et al 53 conducted similar studies in cadaver models to evaluate the efficacy of SPIWay® Endonasal sheaths in mitigating aerosol dispersion caused by endonasal drilling. These endonasal sheaths are typically used to reduce mucosal trauma during endoscopic procedures and to avoid contaminating scope lenses with surgical debris.…”
Section: Discussionmentioning
confidence: 99%
“… Negative pressure systems created from modified ambu masks (negative airway respirator or NAPR) or negative-pressure otolaryngology viral isolation drapes (NOVID). Khoury T, Lavergne P, Chitguppi C, et al 52 Preclinical evaluation of prototypes: proof-of-concept Level 4 (case-control simulation) Risk of Bias: Moderate (incense sticks used may not accurately reflect aerosol/smoke created in OR; difficult to quantitatively measure) NAPR consists of an Ambu mask with a small hole drilled into the front fitted with suction. Tested in the cadaver model only.…”
Section: Methodsmentioning
confidence: 99%